Hierarchical nitrogen-doped porous carbon incorporating cobalt nanocrystal sites for nitrophenol reduction. (18th May 2020) - Xing, Liwen; Gao, Hongyi; Chen, Xiao; Jia, Dandan; Huang, Xiubing; Yang, Mu; Dong, Wenjun; Wang, Ge
Graphical abstract: Highlights: Hierarchical Co-embedded porous carbon microspheres were controllably synthesized. The Co-based catalyst showed superior performance beyond noble-metal-based catalysts. The partially uncovered and totally in-built Co species were likely the active sites. Abstract: The direct pyrolysis of metal organic frameworks (MOFs) has recently provided an effective method to prepare various metal-incorporated composite carbon materials. In this work, hierarchical Co-embedded N-doped porous carbon microspheres were synthesized by controlled pyrolysis of bimetallic Zn-Co Prussian blue analogues (PBAs), in which the metallic Zn component served as thermally removable template and ligand [Co(CN)6 ] 3− served as both Co and N sources. When devoted to catalyzing the reduction of 4-nitrophenol (4-NPh) into 4-aminophenol (4-APh), the optimized catalyst exhibited a large apparent rate constant of 1.35 min −1 and high turnover frequency (TOF) of 0.0204 s −1, which was superior to the majority of noble-metal-based catalysts. Besides, a home-made continuous flow catalysis system was readily constructed. Control experiments confirmed that both partially uncovered and totally in-built active metallic Co species acted as catalytically active sites. This work might provide a further understanding of the identification of active sites within metal-incorporated carbon-based catalysts.